'Education is the land I give them' – mothers' investments in children's future livelihoods amid growing land competition in rural Uganda. Issue 1 (2nd January 2022) - L'Roe, Jessica; Kimambo, Niwaeli E; Strull, Rebecca; Kuzaara, Daisy; Kyengonzi, Florence; Naughton-Treves, Lisa
ABSTRACT: In western Uganda, land inheritance has been the key means to bequeath livelihood opportunities to children, but land competition is increasing rapidly. Shrinking parcels and higher prices have made bequeathing land more difficult, especially for women, whose control over land has been customarily limited. We surveyed 50 rural women about their strategies and challenges investing in children's future livelihoods. We present both quantitative and qualitative analysis of their responses. Over 80% believed it is better to invest in education rather than land, to help children secure remunerative off-farm jobs. Mothers wanted the majority of their children to leave the village to seek work elsewhere, equally for sons and daughters. Many also wished to provide a land-based safety net but worried this was no longer possible. Mothers' assets affected both aspirations for and educational attainment of their children, highlighting potential for intensifying land competition to exacerbate inequality.